2015
DOI: 10.1111/hepr.12523
|View full text |Cite
|
Sign up to set email alerts
|

Significance of viral status on prognosis of hepatitis B‐related hepatocellular carcinoma after curative resection in East Asia

Abstract: Tumor recurrence remains one major obstacle for further improving the prognosis of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) patients after curative liver resection. It has been widely reported that tumor size, positive surgical margin, macroscopic vascular invasion, tumor-node-metastasis stage and Edmondson's grade were significantly related to HCC recurrence. However, the association between HCC recurrence and important viral factors, including the HBV DNA levels, status of hepatitis B s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Studies have shown that chronic hepatitis B virus (HBV) infection is a major risk factor for the development of cirrhosis and HCC [5]. High hepatitis B surface antigen (HBsAg) levels and high serum HBV DNA load were found to increase the risk of HBV-related cirrhosis and HCC significantly [6, 7]. Basic research found that HBV-initiated tumorigenesis may play a role in the development of HCC microvascular invasion [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that chronic hepatitis B virus (HBV) infection is a major risk factor for the development of cirrhosis and HCC [5]. High hepatitis B surface antigen (HBsAg) levels and high serum HBV DNA load were found to increase the risk of HBV-related cirrhosis and HCC significantly [6, 7]. Basic research found that HBV-initiated tumorigenesis may play a role in the development of HCC microvascular invasion [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The age cut-off was set as 55: Young (aged <55 years) and old patients (aged ≥55 years). The grading system used was Edmondson grade (14). The TNM staging system refers to the newest NCCN guidelines (15).…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 ] Various factors, including a high load of HBV-DNA, are considered a risk for HCC recurrence after radical therapy. [ 7 ] In recent years, several studies have indicated that a high HBV-DNA load predicts HCC recurrence after curative resection. [ 8 , 9 ] However, few studies have evaluated the effectiveness of postoperative anti-HBV therapy on tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%